PENILAIAN KESEHATAN PUSAT KOPERASI KARTIKA SRIWIJAYA BERDASARKAN PERATURAN DEPUTI BIDANG PENGAWASAN KEMENTERIAN KOPERASI DAN UKM REPUBLIK INDONESIA NOMOR 06/PER/DEP.6/IV/2016 - mursalin mursalin; Yancik Syafitri (Universitas Tridinanti, 2021)
This study aims to assess the health of the Kartika Sriwijaya Cooperative Center for the 2019 financial year based on the Regulation of the Deputy for Supervision of the Ministry of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia Number 06/Per/Dep.6/IV/2016 concerning Capital Aspects, Quality of Earning Assets, Management, Liquidity, Efficiency, Independence and Growth, and Cooperative Identity. The research method uses descriptive qualitative. The research sample is the financial report of the Kartika Sriwijaya Cooperative Center for the 2019 financial year. The source of the research data is secondary data. Data collection techniques are interviews and documentation. The data analysis technique is descriptive qualitative. Based on the results of the study, it was shown that the health assessment of the Kartika Sriwijaya Cooperative Center for the 2019 financial year received a final score of 60.5, where the score was categorized in the predicate under supervision with details: (1) the capital aspect scored 12.00 with the predicate quite healthy; (2) the quality aspect of earning assets gets a score of 8.75 with a predicate under supervision; (3) the management aspect gets a score of 15.00 with a healthy predicate; (4) the efficiency aspect gets a score of 8.00 with the predicate quite healthy; (5) the liquidity aspect gets a score of 3.75 with a predicate under special supervision; (6) aspects of independence and growth get a score of 6.00 with the predicate quite healthy; and (7) the identity aspect of the cooperative gets a score of 7.00 with the predicate quite healthy.Keywords:Capital, Earning Asset Quality, Management, Liquidity,Efficiency, Independence and Growth, and Cooperative Identity